Probing the Manipulated Neurochemical Drive in Alcohol Addiction and Novel Therapeutic Advancements - Chouhan D.; Uniyal A.; Gadepalli A.; Akhilesh; Tiwari V.; Agrawal S.; Roy T.K.; Shaw S.; Purohit N.; Tiwari V. (My University, 2025)
Alcohol addiction is one of the highly prevalent neurological disorders and a major threat to public health in the 21st century. Alcohol addiction affects people from all age groups and often leads to other serious comorbidities. The pathophysiology of alcohol addiction involves imbalance between the excitatory and inhibitory neurotransmitters in the brain. These changes occur in various regions of the brain including reward circuit such as the ventral tegmental area (VTA), nucleus accumbens (NAc), and prefrontal cortex. In this review, we have discussed several neurochemical circuitries which get manipulated and maladapted during alcohol addiction. To date there is no effective therapeutic intervention in clinics devoid of side effects that can successfully treat the patients suffering from alcohol addiction. Understanding the neurobiological intricacies of alcohol addiction is critical for the development of novel anti-addiction therapeutics. Apart from this, we have also discussed the recent therapeutic milestones for the management of alcohol addiction including vasopressin receptors, corticotrophin-releasing factor, GABA receptors, glucocorticoid receptors, brain stimulation and mindfulness-oriented recovery enhancement. © 2020 American Chemical Society.